Hereditary nephropathy in an English Cocker Spaniel - de Brot, Simone; Adamany, J.; Baiker, Kerstin; Allegrucci, Cinzia; Polledo, L.; Grau-Roma, Llorenc (American Veterinary Medical Association, 2015)
A thirteen-month-old male neutered orange roan English Cocker Spaniel dog was euthanized due to a prolonged history of lethargy, weight loss, severe azotemia and marked proteinuria, which was suggestive of chronic renal failure. At necropsy, both kidneys were pale tan and presented with a diffusely rough and granular appearing surface. Histologically, both kidneys showed severe, generalized, segmental to global, chronic membranoproliferative glomerulonephritis with glomerulosclerosis and proteinuria. DNA was extracted from hair follicles collected at necropsy, and a PCR amplifying exon 3 of gene COL4A4 was performed. The PCR showed that this dog had a homozygous mutation at the position 115 of the gene COL4A4, indicating that this dog suffered from hereditary nephropathy.